2014
DOI: 10.1590/s1806-37132014000400004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of von Willebrand factor in COPD patients

Abstract: OBJECTIVE: To compare the absolute serum von Willebrand factor (vWF) levels and relative serum vWF activity in patients with clinically stable COPD, smokers without airway obstruction, and healthy never-smokers. METHODS: The study included 57 subjects, in three groups: COPD (n = 36); smoker (n = 12); and control (n = 9). During the selection phase, all participants underwent chest X-rays, spirometry, and blood testing. Absolute serum vWF levels and relative serum vWF activity were obtained by turbidimetry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…This is in line with a previous study showing increased VWF activity in symptomatic subjects, but interestingly no change in total VWF was found in that study. 8 We speculate that this is due to the endothelial release of VWF being a more dynamic process, while total VWF reflect a ratio between synthesis and degradation of VWF, which might not be significantly changed in symptomatic disease. Notably, no change was observed of either VWF biomarker when dividing the cohort into GOLD severity groups.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This is in line with a previous study showing increased VWF activity in symptomatic subjects, but interestingly no change in total VWF was found in that study. 8 We speculate that this is due to the endothelial release of VWF being a more dynamic process, while total VWF reflect a ratio between synthesis and degradation of VWF, which might not be significantly changed in symptomatic disease. Notably, no change was observed of either VWF biomarker when dividing the cohort into GOLD severity groups.…”
Section: Discussionmentioning
confidence: 86%
“…This was also highlighted by the fact that VWF-A had a better association with symptomatic disease than VWF-N. Previous studies have found VWF-antigen but not VWF activity, 8 to be increased in exacerbating patients. 34,35 The VWF-A assay targets a neo-epitope within the A2-domain of VWF, which arises from ADAMTS13-cleavage which is specific for active VWF.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Levels are increased in smokers and fall to non-smoker levels 3-6 weeks after smoking cessation. Von Willebrand factor vWF Related to thrombosis and CVD (O'Callaghan et al 2005) (especially in CVD patients) as well as respiratory disease (Bartholo et al 2014, Holz et al 2014. Only limited evidence that smoking cessation leads to a decrease in vWF levels.…”
Section: Apolipoprotein A1 Apoa1mentioning
confidence: 99%
“…Αντιθέτως, τα επίπεδα παρόξυνσης τόσο του vWF:Ag όσο και της CRP, συσχετίσθηκαν σημαντικά με το βαθμό δύσπνοιας κατά mMRC, ενώ επιπροσθέτως το χρονικό διάστημα μέχρι την εμφάνιση της πρώτης παρόξυνσης διαφοροποιήθηκε σημαντικά μεταξύ των ασθενών με τις υψηλότερες και χαμηλότερες τιμές του vWF:Ag. Τα ευρήματα αυτά είναι συμβατά με μελέτες που έχουν δημοσιευθεί στο παρελθόν, οι οποίες έχουν συσχετίσει τους συγκεκριμένους βιοδείκτες με διάφορες παραμέτρους βαρύτητας της νόσου[213,221,[224][225][226].Αξίζει τον κόπο να γίνει αναφορά στο γεγονός ότι, αν και όχι σε επίπεδο στατιστικής σημαντικότητας, τα επίπεδα της ενδοκάνης ήταν υψηλότερα κατά την παρόξυνση σε σχέση με τη σταθερή νόσο, καθώς και στους ασθενείς με ΧΑΠ έναντι των μαρτύρων. Οι παρατηρήσεις αυτές βρίσκονται σε συμφωνία με τη θεωρία που υποστηρίζει την επιδείνωση της ενδοθηλιακής δυσλειτουργίας κατά τις παροξύνσεις, η οποία έχει επιβεβαιωθεί σε μελέτες, με τη χρήση του δείκτη της διαμεσολαβούμενης από τη ροή του αίματος αγγειοδιαστολής (FMD) και βιοδεικτών όπως ο vWF[135,227,228].…”
unclassified